Yours, mine or ours? : a study of intra family income distribution : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Policy at Massey University, Albany Campus - Switzer, Pauline Kay (Massey University, 1998)
Access accorded to family members to the resources of the household are an aspect of distribution which reflects the structure and values of a society. This thesis is an examination of the issues surrounding intra family income distribution. A significant aspect of this broad issue of distribution and the way in which it reflects inequalities in our society, is the use of statistical data on income and its distribution as a base for policy, without examination of the reality of access to economic resources for women. There are traditional assumptions of joint decision making by husbands and wives which influence policy decisions, and these assumptions need to be examined in the light of evidence from research, to determine the extent to which they can be justified. This thesis is based on three foundation studies conducted in Australia (Edwards, 1981), Britain (Pahl, 1989), and New Zealand (Easting and Fleming, 1994), about intra family income distribution, which challenge the traditional assumptions. A qualitative study was carried out for this thesis, employing a feminist perspective within a framework of critical social science and grounded theory, to investigate the systems of pooling of money in four New Zealand households. The thesis considers the findings of this study, and relates them to the three foundation studies conducted earlier in Australia, Britain and New Zealand. The thesis concludes with recommendations for policy and future research.
Keywords: New Zealand; Family -- Economic aspects; Households -- Economic aspects; Income distribution